Diffuse malignant peritoneal mesothelioma: A review - Sun, Luanbiao; Li, Chenguang; Gao, Shuohui (Frontiers in Surgery, 2023)
Diffuse malignant peritoneal mesothelioma (DMPM) is an unusual and life-threatening locally invasive tumor. The morbidity and mortality of the disease are associated with progressive local effects in the abdominal cavity, such as abdominal distention, painful sensations, and early saturation with reduced oral intake, which eventually lead to intestinal obstruction and cachexia. Computed tomography (CT) has been widely used as a first-line diagnostic tool for DMPM. In addition, the most sensitive immunohistochemical markers of DMPM include WT 1, D2-40, and calmodulin. This paradigm has altered with the advancements in the immunohistochemical analysis of BRCA1-Associated Protein 1 (BAP1) the lack of BAP1 expression shows the diagnosis of malignancy. DMPM is resistant to conventional chemotherapies. Therefore, the gold standard for the treatment of DMPM is the combination of cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). The overexpression of the phosphatidylinositol 3-kinase (PI3K)/AKT serine/threonine kinase 1 (AKT)/mammalian target of rapamycin (mTOR) signaling pathway drives the malignant phenotype of DMPM, thereby showing promising potential for the treatment of DMPM. The coordinated activities among multiple RTKs are directly involved in the biological processes of DMPM, suggesting that the combined inhibition of the PI3K and mTOR signaling pathways might be an effective measure. This treatment strategy can be easily implemented in clinical practice. However, the combined inhibition of ERBB1(HER1)/ERBB2 (HER2) and ERBB3 (HER3) requires further investigations. Thus, based on these, the discovery of novel targeted therapies might be crucial to improving the prognosis of DMPM patients.